Pedagogical Support in Human Talent Management: A Systematic Review - Córdova, Mgs. Milquiades Enrique Roña; Orozco, Mgs. Evert Peña; Castillo, Mgs. Juan Alberto Castillo (Journal of Ecohumanism, 2024)
This systematic review explored the impact of pedagogical coaching on human talent management and teacher performance over the past four years. A qualitative approach was employed using the PRISMA methodology to conduct searches in the following databases: Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex, the University of César Vallejo library, and other relevant databases. Inclusion and exclusion criteria were applied. For inclusion, articles published between 2021 and 2024 that addressed pedagogical coaching in the context of human talent management and teacher performance were considered, while studies that did not focus on educational contexts, were not peer-reviewed, or were not available in full text were excluded. Through the analysis of 229 studies, it was found that pedagogical coaching has a positive effect on improving teaching practices and teacher satisfaction. However, the effectiveness of coaching varies depending on the context and the quality of its implementation. The results suggest the need to strengthen the training of coaches, personalize support, and establish clear regulatory frameworks to ensure the quality of coaching. This review contributes to consolidating pedagogical coaching as a key strategy to improve educational quality and teacher professional development.